THE EFFECTIVENESS OF USING VYMPEL-2 GROWTH REGULATOR AND COMPLEX MICRO-FERTILIZER ON SOYBEAN SOWN AREAS - Laslo, O. O.; Melnychuk, A. V. (Scientific Progress & Innovations, 2021)
Numerous researches in agronomic practice on the influence of plant growth regulators and mixtures with micro-fertilizers contribute to a new search for combinations and their application rates to increase soybean productivity and improve grain quality indicators. Studies of this issue highlight the advantages and disadvantages of preparations combinations of both synthetic (chemical) and natural origin and their use on legume crops sown areas. The following drawbacks were detected in mixtures of PPP, micro-fertilizers and herbicides: the inhibition of their action and reduction of phytotoxic effect on weed component. There are much more advantages of using such combinations, as evidenced by numerous research results on this issue, among which the main are the increase in seed germinating power and crop productivity. The article presents data on the peculiarities of the impact of the mixture of Vympel-2 growth regulator and Oracul micro-fertilizer of complex action on Romashka soybean variety productivity. The effectiveness of mixtures varied depending on the methods of their applying, but the most significant was the impact of soybean seed treatment at the rate of Vympel-2 (500 g/t) + Oracul multi-complex (1 l/t) in combination with vegetation treatment with Vympel-2 (500 g/ha) + Oracul multi-complex (1 l/ha), at which the number of soya beans and seed weight on the plant increased by 23 %; 24.9 % in comparison with the control, and the yield – by 26.2 %. The application of only Vympel-2 growth regulator at soybean seed treatment contributed to improving the indicators by 7.7%, 7.4%, and 9.7%. The application of the composition of Vympel-2 (500 g/t) + Oracul multi-complex (1 l/t) for seed treatment allowed to increase the indicators by 15.7 %; 23.2 %; 20.5 % in comparison with the control. However, there was a decrease in the studied indicators for the composition of Vympel-2 (500 g/ha) + Oracle multi-complex (1 l/ha) during vegetation treatment in comparison with the previous variant (seed treatment). The indicators on variant 3 exceeded the control by 14 %; 20.8 %; 19.1 %. It has been established that the use of pre-sowing soybean seed treatment with mixtures of Vympel-2 (500 g/t) + Oracul multi-complex (1 l/t)) in combination with the application of the preparations during the growing season (Vympel-2 (500 g/ha) + Oracul multi-complex (1 l/ha)) favors the increase in crop productivity indicators in comparison with the variants, in which the preparations were applied both separately and in separate phases of soybean plant development. The combination of the preparations and their application in two terms undoubtedly made it possible to disclose the potential of the variety, as evidenced by the increase in crop yields and productivity indicators.